STRENGTHENING COMMUNITY ENGAGEMENT THROUGH NEIGHBORHOOD ASSOCIATION HEADS’ COMMUNICATION - Dema, Yosef; Prastio, Wiwin; Billy, Yohanes Langgar (Jurnal Komunikasi dan Bisnis, 2023)
This study aims to promote community engagement through government communication from RT heads. Some RT leaders seek to enhance community engagement, while others fail to carry out their duties. To provide critical-descriptive analysis, data was collected using qualitative methods such as observation, interviews, and documentation procedures. As a result, the government's communication strategy of combining face-to-face contact, exemplary communication by RT heads, and dialogic communication that positions RT inhabitants as RT partners was successful in boosting residents' support for PMI and Bazis fundraising targets. It was determined that the RT heads' communication and leadership were significant factors in developing community support and engagement.